When young children need help : understanding and addressing emotional, behavioral, and developmental challenges - Hirschland, Deborah (St. Paul, MN : Redleaf Press, 2015)
"Learn how to reach children who need special help. Almost anyone who works with 3- to 6-year-olds knows what it feels like to spend time with youngsters who are particularly puzzling or hard to help. When Young Children Need Help examines how early childhood educators can make sense of what is going on for such children and then use that understanding to help promote growth and mastery. Written for child care center staff, family child care providers, preschool teachers, and pre-service teachers, this book can be useful to any adult who wants to learn more about reaching the most troubling children in his or her care. When Young Children Need Help provides a framework for understanding a range of emotional, behavioral, and developmental challenges. It explores a process through which early childhood teachers and providers can translate their growing understanding of a child's difficulties into sensible goals for intervention. The author lays out practical strategies that help kids connect and communicate with ease, focus their attention, manage their bodies and their feelings, engage in constructive problem-solving, and experience themselves as successful friends and learners. The book suggests approaches for collaborating with parents and other caregivers and emphasizes that even when a child needs outside services and supports, what goes on in school or care remains central to making progress. Ranging from the classroom to the playground and back again, When Young Children Need Help offers its perspectives and strategies through highly engaging stories that bring challenging kids alive in all their quirky uniqueness."--
"A close look at how early childhood educators can make sense of what is going on with puzzling or hard-to-help children, and use that understanding as a springboard for promoting growth and mastery"--
Machine generated contents note: pt. 1 Getting Specific Before Getting to Work -- ch. 1 From Reflection to Action: Looking Closely, Thinking Clearly, Intervening Effectively -- ch. 2 Generating "Maybes": Observing with Depth, Breadth, and an Eye for Surprises -- ch. 3 Spotlight on Development: Understanding the Building Blocks of Early Childhood Mastery -- ch. 4 Spotlight on Causation: Considering the "Whys" behind Worrisome Behavior -- ch. 5 Developing Child-Specific Portraits: Making Sense as the Foundation for Making Progress -- ch. 6 Pathways to Growth: Joining Big-Picture Thinking with Practical Strategies -- pt. 2 Connection Is Key -- ch. 7 Spotlight on the Three Cs: Connection, Communication, and Cue Responsiveness -- ch. 8 Getting to Work with Hannah: Helping a Child with Dark Moods and a Dark Past -- ch. 9 Getting to Work with Hannah, Continued: "Seeding the Day with Connection" and Other Strategies -- ch. 10 Getting to Work with Jenny: Helping an Intensely Shy Child -- ch. 11 When Home Has Been Hard: Helping Children Climb (or Re-climb) Developmental Ladders -- ch. 12 When Language Is Limited: Helping Two Boys Who Struggle to Communicate -- pt. 3 Addressing Problems in Self-Regulation -- ch. 13 Getting to Work with Gabrielle: Helping Out When Energy Is High and Focus Is Low -- ch. 14 Getting to Work with Brian: Helping an Easily Frustrated Child -- ch. 15 Getting to Work on "Big Feelings": Helping Children Who Get Swamped by Anger or Anxiety -- ch. 16 Spotlight on Parenting: Helping Families Set Effective Expectations at Home -- pt. 4 Putting It All Together -- ch. 17 A Letter about Sam: Helping a Child with Multiple Challenges -- ch. 18 When Young Children Need Help: Big Changes Start with Small Steps.
Includes bibliographical references (pages 295-297) and index.
Keywords: Problem children -- Education (Elementary); Behavior disorders in children; Emotional problems of children; Behavioral assessment of children; Early childhood education; Educational psychology; EDUCATION -- Special Education -- General; EDUCATION -- Preschool & Kindergarten; EDUCATION -- Classroom Management